ANALISIS TINDAK TUTUR EKSPRESIF PADA DAFTAR PUTAR VIDEO KULIAH NEGOSIASI DALAM CHANNEL YOUTUBE KULIAH KEHIDUPAN - Utomo, Asep Purwo Yudi; Azki Akhmad Mafaza; Novana Ika Puspita; Fadhila Ramadhani; Diyas Bagus Firmansyah; Riyadi Widhiyanto; Rossi Galih Kesuma (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2024)
Pragmatics is a field of linguistic study that relies on context as the main means of understanding an intention. One of its areas of study is expressive speech acts, which are used to express or convey someone's emotional and feeling states. The aim of this research is to describe and analyze various types of expressive speech acts found in the "Negotiation Lecture" videos on the "Kuliah Kehidupan" YouTube channel. This research employs a qualitative descriptive methodological approach and a theoretical pragmatic analysis approach. The data sources used are derived from conversations or expressive utterances found in the negotiation lecture videos on the "Kuliah Kehidupan" YouTube channel. Data collection in this article uses the observation and note-taking technique. The data analysis technique employs distributional and matching techniques. The results of this research found ten types of speech acts in the "Negotiation Lecture" videos on the "Kuliah Kehidupan" YouTube channel, namely expressive speech acts of criticizing, hoping, complaining, blaming, praising, apologizing, thanking, expressing anger, congratulating, and expressing fear. This research is beneficial for providing new insights into the classification of expressive speech acts found in the videos. It is expected that this research can serve as a reference for students, lecturers, or learners, and as material for further research in the context of learning in pragmatic studies, especially regarding the types of expressive speech acts.